O projeto didático de José Luiz Fiorin para o ensino de leitura e de produção de texto - Cortina, Arnaldo [UNESP] (FapUNIFESP (SciELO), 2015)
In September of 2014, a group of professors and researchers met to reflect on the contributions that the works published by José Luiz Fiorin bring to the study of discourse, text and to the progress of research in semiotics. This work, with which I joined in the Colloquium, aims to analyze how the didactic project established by this scholar of language's manifestations is relevant for the teaching and reading of text production. Besides, it also reflects the progress made by Brazilian and foreign semioticians concerning the improvement of the methodological project held by this theory, which investigates the constitution of the meaning of texts.
José Luiz Fiorin's Didactic Project for the Teaching
Keywords: Didactic Work; Fiorin; Reading; Semiotics; Text Writing